1344. Ridinilazole (RDZ) for Clostridium difficile Infection (CDI): Impact of Diagnostic Method on Outcomes From a Phase 2 Clinical Trial. (26th November 2018) - Vickers, Richard; Chowdhury, Sumita; Wilcox, Mark
Abstract: Background: Diagnosis of CDI includes fecal detection of a C. difficile toxigenic strain (TS) or free toxins (FT). TS detection does not distinguish infection from colonization. Guidelines recommend an FT test be part of diagnostic algorithms. Here we report outcome differences, based on diagnostic method at enrollment, from a Phase 2 clinical trial of RDZ, a novel CDI antibiotic designed to treat CDI and reduce recurrence of CDI (rCDI). Methods: This double-blind study randomized 100 patients 1:1 to 10 days RDZ 200 mg BID or vancomycin (VAN) 125 mg QID treatment. Subjects were enrolled with CDI symptoms and a positive diagnostic result (FT or TS). Baseline (BL) stool samples were assessed for the presence of FT. All subjects entered the intent to treat (ITT) population; those subjects positive for FT entered a modified ITT (mITT), the primary analysis population. Primary endpoint was sustained clinical response (SCR) defined as cure at end of therapy and no rCDI for the next 30 days. rCDI was defined as CDI symptoms, a positive diagnostic test and need for therapy; a sensitivity analysis considered positive FT rCDI cases. BL fecal concentrations of lactoferrin and calprotectin were determined by enzyme immunoassay. Results: Of 100 subjects enrolled, 69 (36 RDZ: 33 VAN) were FT positive at BL. RDZ compared with VAN recipients had improved SCR rates via reduced rCDI. Absolute differences in SCR between RDZ and VAN (prespecified 90% CI) for MITT (FT positive) and ITT subjects were 24.3% (3.1, 39.1) and 14.0% (−1.8, 28.8), respectively. Absolute SCR differences between the MITT and ITT subjects from the sensitivity analysis were 26.2% (4.6, 40.6) and 14.3% (−1.7, 29.1). Median BL calprotectin and lactoferrin levels (µg/mL) were significantly higher for FT positive subjects at 1, 002 and 87, than for FT negative subjects at 53 and 4, respectively. Conclusion: RDZ showed improved SCR in comparison with VAN. Treatment differences were greater in MITT subjects. Lower SCR improvement in RDZ ITT subjects is likely due to enrollment of some colonized rather than infected subjects; this explanation is supported by higher calprotectin and lactoferrin levels in FT-positive samples. These data demonstrate the importance of FT testing in-line with CDI guideline recommendations. Disclosures: R. Vickers, Summit Therapeutics: Employee, Salary and Stock options. S. Chowdhury, Summit Therapeutics: Employee, Salary and Stock options. M. Wilcox, Summit Therapeutics: Consultant, Research Contractor and Scientific. Advisor, Consulting fee, Research grant and Research support.